A Chronological List of References on Switched Capacitor Networks and Techniques for the Period 1981-1992. (1994) - Singh, A. K.
Abstract : A chronological list of 440 references on switched capacitor (SC) networks from 1939 to May 1981 was published in this Journal by J. Vandewalle. In this communication, we present a compilation of 1357 references covering the period from May 1981-1992 (along with a supplementary list of 43 missing references for the period before May 1981). The present compilation and the earlier one by Vandewalle put together, thus, constitute an exhaustive bibliography of 1797 references on SC-networks and techniques till 1992.